Obligation Of Giving Alimentation To Increased Children Due To Parents' DIvorce (Study of PT JAKARTA Decision Number 450/PDT/2019/PT DKI) - Sonia Yekti Hapsari; Misbahul Huda (Fakultas Hukum Dehasen, 2022)
In the event of a divorce between husband and wife, legally their relationship is broken as husband and wife. But on the contrary, regarding the legal relationship with their children, even though they are divorced, it means that the parents still have rights and obligations towards the abandoned child. The impact of divorce does not only occur in the present, but also affects the lives of children in the future. Children as the nation's buds are the next generation in the development of the nation and state. Children cannot stand alone, it is necessary to make efforts for child welfare so that they can grow and develop properly both spiritually, physically and socially. In the example of the DKI Jakarta High Court Decision Number 450/PDT/2019/PT DKI, Sentencing that the parents (father) provide living expenses/maintenance (alimentation) and education costs for a child named Bennedict Dayton Lim in the amount of Rp. 8,000,000.00 (eight million). rupiah) per month until the child is an adult, which is given through the Appellant/originally the Plaintiff no later than the 5th day of the month..